Nadzieja i optymizm vs zwątpienie i pesymizm w kontekście „dobrego życia” w kulturze konsumpcji - Kasperek-Golimowska, Ewa (Wydawnictwo UAM, Adam Mickiewicz University Press., 2012)
Defining and describing the manifestations of the good life, as well as reflecting on the complexity of the factors that let one’s life to be defined as a good one, are the area of interest of the positive psychology. Their representatives seek answers to many questions related to the research on the possibilities of achieving a sense of well-being by a modern man. What is the good life? If and how you can help people live better lives?What are the characteristics and sources of the good life?What does it mean to be happy, to live happily? Is there a personality of a happy man and how to define it?What qualities and values of people make their lives more satisfying, enjoyable and productive? If and how you can develop, strengthen and improve the skills to live happily? And what determines the well-being, happiness and life satisfaction? There are many answers to these questions in the literature.Also, the research findings are not unambiguous.In the area of the contemporary culture you can often encounter the idea that the good life is ”the life filled with goods”. The result is a prevailing belief of on many people that happiness and welfare are derived from ”the wealth, buying, accumulating, use of technological innovations, services and other material goods”.However, there are also conditions for the emergence of the individuals and social groups that identify ”the good life” with the possession and/or development of personal qualities (virtues, strength of character, resources), such as enthusiasm and optimism, emotional intelligence, hope, faith and spirituality, etc. Which of these approaches has a stronger influence of one’s happiness? What values ought to be promoted and in what direction the personal, social and civilization development should be stimulated in order to make it possible for a modern man to live ”the good life” and to participate in the creation of the educational environment that gives a chance for the self-actualization? The aim of this article is an attempt to answer these questions on the basis of selected works in the field of positive psychology.
Hope and optimism vs. despair and pessimism in the context of the „good life” in the culture of consumption
Keywords: dobrostan; well-being; szczęście; happiness; dobre życie; good life; nadzieja; hope; optymizm; optimism; pesymizm; pessimism; kultura konsumpcji; culture of consumption